MENINGKATKAN MINAT BELAJAR DENGAN MENGGUNAKAN MEDIA WORDWALL KELAS 4 DI SEKOLAH DASAR - Setyorini, Diyah; Suneki, Sri; Prayitno, Muhammad; Prasetiawati, Catur (JURNAL SINEKTIK, 2024)
Research objective: to build interest in learning in elementary school children with technology-based, namely Wordwall, nowadays almost all children in elementary schools like to play online games on cell phones/gadgets, for this reason this method can be applied to children in elementary schools to divert children's habits so as not to get addicted to online games and make interest in learning better. the basic factor that affects children's learning interest is low, namely boring teaching techniques. The homeroom teacher there only uses YouTube, PPT in teaching. After the Wordwall Media was applied to elementary school level children, especially at SDN Panggung lor grade IV to increase their interest in learning at school, it became high. Indirectly WordWall can also be used to assess knowledge besides learning students can also play online games like WordWall. The researcher used a qualitative method through observing the homeroom teacher for class IV at SDN Panggung Lor and giving questionnaires to students to find out students' interest in learning through the WOrdWall media. The results of this study using educative online game-based learning media can increase students' interest in learning. Keywords: Interest in Learning1; WordWall2; Online game3